Chemical and Radiological Characterizations of the Desert Dust Coming from Northern Africa to Batman (Southeastern Turkey) - Isik, Umit; Çevik, Uğur; Akkoca, Dicle Bal; Oguz, Kahraman; Damla, Nevzat (My University, 2022)
This work investigates the chemical and radiological characterizations of the dust coming from Sahara in North Africa to Batman city in the southeastern region of Turkey on 20 May 2017. According to meteorological maps, the source region of the dust storm that took place in Batman was found to be Libya, which is supported by the NOAA HYSPLIT model’s back trajectory analysis. XRD analyses show that the common minerals of the dust samples are quartz, feldspars, calcite, dolomite, hematite and rutile. Chemical patterns of some major, minor and trace elements in dust samples are generally consistent with those of Saharan Dust composition. The heavy metals in the dust follow the decreasing concentration order: Mn > Zn > Cr >Ni > Cu > Pb. The enrichment factors (EF) of these elements show anthropogenic contamination effects with regard to Zn, Cr and S elements in dust samples. The corresponding values of the radionuclides, the absorbed dose rates in the air and the annual effective doses in the samples were also evaluated and compared to the internationally recommended values. The findings are supposed to be beneficial for tracking and evaluating any environmental pollution inventory in this area.
Keywords: Radioactivity; Dust; Chemical analysis; Enrichment factor; Trajectory analysis.